Ovartaci the signature of madness - Hansen, Brian Benjamin (Aarhus University Press, 2022)
Hospitalized following a mental health crisis in 1929, Louis Marcussen (1894—1985) begins a spectacular journey. He fills his room at the psychiatric institution with artworks, with tall and eloquent cut-out female figures, and he seems to invest himself deeply in his work and visions. He dissolves into a swirl of male, female, animal and divine identities. He discards the name ‘Louis’ and takes the name ‘Ovartaci’. The present book reads Ovartaci’s work through psychoanalytical notions of madness and psychosis. It is the first major monograph on an artist that through highly original artistic practices invented a new way of living. Brian Benjamin Hansen is a postdoctoral researcher at Aarhus University and senior associate professor at VIA University College. Ovartaci is increasingly recognized as one of the most enthralling Danish artists of the 20th century. At the 2022 Venice Biennale, the art of Ovartaci is part of the main exhibition and displayed in the Central Pavilion.
Keywords: Ovartaci -- 1894-1985; Malerei; Papiermaché